KONSTRUKSI Al-‘UQU - Umam, Khoerul; Triana, Nita; Alfiani, Melita Elza (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2022)
Management of Hajj funds for investment is a necessity that must be done to subsidize the shortage of costs for organizing the Hajj. This type of research is field research (field research) where researchers collect data directly from the field, the community, Bank MuamalatPurwokerto which is the object of research that studies intensively the background conditions that occur in accordance with the research theme. Furthermore, the place used for research was Bank Muamalat Purwokerto Branch and this research was conducted from December 20 2021 to November 20 2022. The approach used by researchers is a qualitative approach to measure data in terms of quality. The primary sources in this study were interviews with 10 customers who registered for the pilgrimage at Bank MuamalatPurwokerto and interviews with the leadership of Bank MuamalatPurwokerto, Mr. Bambang Haryonugraha. The secondary sources used by researchers were journals, books or others related to the research theme. The investment made by BPKH is a must because the contract used between the three parties is in accordance with the Shari'a and the resulting benefits can be felt by all parties, especially the prospective pilgrims.